Perancangan Sistem Informasi Posyandu Aster XI Desa Saga Berbasis Java - Yonofa Putra, Fitrada; Sandy, Agung Ferdinan; Primawati, Alusyanti (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
Health is a need that must be met for all Indonesian people. A healthy body and mind are needed to support all activities. The Health service activities at Posyandu (Integrated health services post) Aster XI are still conducted manually or written by hand, from the collection to process of the data. This can hinder and cause many problems in the processing, searching and producing reports on Posyandu Aster XI activities. Thus, it is necessary to develop the conventional systems to become computerized. The research method used is Grounded Research, while the system development method used is waterfall. The aim of this research is to design and implement a Java-based information system at Posyandu so that it can help and speed up work in terms of processing data such as storing, changing and searching data to making reports at Posyandu Aster XI. The result of this research is the use of a computerized system, created with the Java programming language and MySQL database, that can help and make cadres process the data at the Posyandu more quickly, precisely and efficiently.